Sustained inhibition of the NaV1.7 sodium channel by engineered dimers of the domain II binding peptide GpTx-1. Issue 21 (1st November 2015) - Murray, Justin K.; Biswas, Kaustav; Holder, J. Ryan; Zou, Anruo; Ligutti, Joseph; Liu, Dong; Poppe, Leszek; Andrews, Kristin L.; Lin, Fen-Fen; Meng, Shi-Yuan; Moyer, Bryan D.; McDonough, Stefan I.; et al.
Graphical abstract